2013
DOI: 10.1212/wnl.0b013e3182a824f7
|View full text |Cite
|
Sign up to set email alerts
|

Episodic migraine and obesity and the influence of age, race, and sex

Abstract: The odds of EM are increased in those with obesity, with the strongest relationships among those younger than 50 years, white individuals, and women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
110
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(121 citation statements)
references
References 31 publications
9
110
1
1
Order By: Relevance
“…A study of 30215 subjects found migraine symptoms in 3791; there was no association between migraine prevalence and increased BMI but an association was found between increased body weight with increased headache incidence and pain severity (25). A recent study in similar age groups found a relationship between migraine and obesity (26,27). Several adipocytokines are released from adipose tissue.…”
Section: Migraine In the Presence Of Insulin Resistance And Obesitymentioning
confidence: 99%
See 1 more Smart Citation
“…A study of 30215 subjects found migraine symptoms in 3791; there was no association between migraine prevalence and increased BMI but an association was found between increased body weight with increased headache incidence and pain severity (25). A recent study in similar age groups found a relationship between migraine and obesity (26,27). Several adipocytokines are released from adipose tissue.…”
Section: Migraine In the Presence Of Insulin Resistance And Obesitymentioning
confidence: 99%
“…In addition, hypothalamic peptides and nutrition-related neurotransmitters such as orexin and adipokines may contribute to the pathophysiology of migraine. Regulation of the release of these peptides and proteins may trigger or contribute to the development of headache in migraine (26).…”
Section: Migraine In the Presence Of Insulin Resistance And Obesitymentioning
confidence: 99%
“…[3][4][5][6] Sphingolipids (e.g., sphingomyelins, ceramides) are a group of bioactive lipids that are critical components of membrane microdomains. 7,8 In addition to important structural roles, these…”
Section: Classification Of Evidencementioning
confidence: 99%
“…While some studies included adults of all ages, [5][6][7] others were limited to younger 3,8,9 or older [10][11][12] populations, whereas others stratified by age (e.g., ,50 and $50 years). 13,14 Likewise, some studies included both men and women (combined or stratified), 1 whereas others were limited to only women. 3,[9][10][11][12] The operational definition of exposure and outcome categories has also varied substantially across studies.…”
mentioning
confidence: 99%
“…3,[9][10][11][12] The operational definition of exposure and outcome categories has also varied substantially across studies. Although most studies reported using the WHO physical status categories, 15 some compared obese individuals (body mass index [BMI] $30) with those who were nonobese (e.g., underweight, overweight, and normal weight combined [BMI ,30]), 12,14 others compared obese (BMI $30) with normal weight (BMI 18.5-29.9) individuals, 3,13 whereas others compared those in partial obesity grades (e.g., BMI 30-34.9, BMI 35-39.9, BMI $40) with normal weight individuals 6,7,9 (table e-1 at Neurology.org).…”
mentioning
confidence: 99%